An overview of food biotechnology in Malaysia. - Abdul Karim, Mohamed Ismail (1989)
Food biotechnology is relatively a new and an emerging field in Malaysia. The early usage or practical application of biotechnology knowingly or unknowingly has long been in existence in the food Industry which employ the manufacture of traditional fermented foods. Today the Food Industry plays a vital role in application of biotechnology to produce or manufacture various food and industrial products. Wide application of biotechnology is found in the Food, Beverage, Dairy and the Baking Industry and somewhat to a lesser extent in the industrial sector. This paper will discuss the present scope and usage of biotechnology in the food industry and the future trend of its application in years to come.